Velocity planning method for position–velocity–time control based on a modified S-shaped acceleration/deceleration algorithm. (17th January 2022) - Ni, Hepeng; Ji, Shuai; Liu, Yanan; Ye, Yingxin; Zhang, Chengrui; Chen, Jiwen
Position–velocity–time control mode has been wildly used in industrial application. And velocity planning is one of the most important factors to determine the performance of position–velocity–time motion. To generate smooth trajectory while satisfying the kinematic constraints of the devices such as the maximum velocity, acceleration, and jerk, a novel velocity planning method is proposed. Firstly, a modified S-shaped acceleration/deceleration algorithm is designed to restrict the kinematic parameters. Meanwhile, a series of rules are specified to constrain the velocity profile to simplify the velocity planning process. On this basis, the velocity planning method is proposed based on the modified acceleration/deceleration algorithm. For reasonable position–velocity–time command, the given position–velocity–time conditions can be satisfied with smooth velocity profile, where the kinematic parameters can be limited in their allowable ranges. For unreasonable position–velocity–time commands, a series of planning strategies are designed to adjust the given conditions according to the user needs, which is suitable for the real application. The comparative experiments show that the proposed method can realize the velocity planning for position–velocity–time motion with smooth trajectory while restricting the kinematic parameters. The computational load is also tested to satisfy the real-time requirement. Therefore, the proposed velocity planning method has good performance and strong practicability.